Use of research in local alcohol policy-making. Issue 4 (7th December 2015) - Rossow, Ingeborg; Ugland, Trygve; Baklien, Bergljot
Abstract : Purpose: – On-premise trading hours are generally decided at the local level. The purpose of this paper is to identify relevant advocacy coalitions and to assess to what extent and how these coalitions used research in the alcohol policy-making process concerning changes in on-premise trading hours in Norway. Design/methodology/approach: – Theory-driven content analyses were conducted, applying data from city council documents (24 Norwegian cities) and Norwegian newspaper articles and broadcast interviews ( n =138) in 2011-2012. Findings: – Two advocacy coalitions with conflicting views and values were identified. Both coalitions used research quite extensively – in the public debate and in the formal decision-making process – but in different ways. The restrictive coalition, favouring restricted trading hours and emphasising public health/safety, included the police and temperance movements and embraced research demonstrating the beneficial health/safety effects of restricting trading hours. The liberal coalition of conservative politicians and hospitality industry emphasised individual freedom and industry interests and promoted research demonstrating negative effects on hospitality industry turnover. This coalition also actively discredited the research demonstrating the beneficial health/safety effects of restricting trading hours. Originality/value: – Little is known about how local alcohol policy-making processes are informed by research-based knowledge. This study is the first to analyse how advocacy coalitions use research to influence local alcohol policy-making.